Redox metabolism: the hidden player in carbon and nitrogen signaling?. (17th February 2020) - Chaput, Valentin; Martin, Antoine; Lejay, Laurence
Abstract: While decades of research have considered redox metabolism as purely defensive, recent results show that reactive oxygen species (ROS) are necessary for growth and development. Close relationships have been found between the regulation of nitrogen metabolism and ROS in response to both carbon and nitrogen availability. Root nitrate uptake and nitrogen metabolism have been shown to be regulated by a signal from the oxidative pentose phosphate pathway (OPPP) in response to carbon signaling. As a major source of NADP(H), the OPPP is critical to maintaining redox balance under stress situations. Furthermore, recent results suggest that at least part of the regulation of the root nitrate transporter by nitrogen signaling is also linked to the redox status of the plant. This leads to the question of whether there is a more general role of redox metabolism in the regulation of nitrogen metabolism by carbon and nitrogen. This review highlights the role of the OPPP in carbon signaling and redox metabolism, and the interaction between redox and nitrogen metabolism. We discuss how redox metabolism could be an important player in the regulation of nitrogen metabolism in response to carbon/nitrogen interaction and the implications for plant adaptation to extreme environments and future crop development. Abstract : This review highlights and discusses the role of redox metabolism in the regulation of nitrogen metabolism in response to both carbon and nitrogen in plants.